Validation of the Cultural Intelligence Self-Assessment Scale in the context of DR Congo-Kinshasa - Christian Lutete Ayikwa (Business Management Analysis Journal (BMAJ), 2022)
The purpose of this study was to validate a Cultural Intelligence (CQ) Self-Assessment Scale in DR Congo. The questionnaire was self-administered to 430 workers in enterprises from both the public and private sector, as well as representing all linguistic groups. When the Principal Component Analysis and orthogonal varimax rotation extraction method were employed to group items in the data set, five factors were extracted but two were removed for poor internal consistency at the exploratory stage. The three factors retained were renamed with regard to the considered CQ aspects, constant awareness (CAW), cultural understanding (CU) and CQ skills (CQS), and estimation of their individual assessment scales at confirmatory factor level led to the deletion of four more items. The final CQ Self-Assessment model fitted well with the data after the errors’ correlation technique was applied to modify the initial model that showed poor fitting statistics. The contextualised CQ Self-Assessment Scale will be an asset in determining workers’ level of CQ and its related aspects in DR Congo. All three underlying dimensions of CQ correlate significantly and positively with each other, with medium size effect, except for CU and CQS that showed small size effect. Recommendations are made to replicate this study beyond Kinshasa Province and preferably integrate the Meta-cognitive component that the study’s instrument did not consider, as well as to administer the questionnaire to workers in the informal sector.